“Verstummt der süssen Stimme Schall”: the Destiny of Four Croatian Singers in the “Long 19th Century” - Vjera Katalinić (Diasporas: Circulations, Migrations, Histoire)
The fate of Ilma de Murska, Irma Terputec-Terée, Emma Wiziak de Nicolesco and Milka Ternina, who were launched out from Croatia into the most prominent world stages, reflects the image of musical culture in this part of the Habsburg monarchy, presents the specific and individual characteristics of their life paths, and indicate some specificities of their time and milieu, ranging from general political and cultural issues, social and financial status, attitudes towards their private lives and personal relations up to entirely musical inclinations.